Law of international trade : cross-border commercial transactions - Chuah, Jason C.T. (United Kingdom: Thomson Reuters, 2023)
Law of International Trade: Cross-Border Commercial Transactions is a well-established title providing readers with a comprehensive and up to date treatment of all key aspects of private international trade law.The seventh edition stays faithful to the book's original rationale by emphasising the link between doctrine and the pragmatics of international commercial law. It offers a thorough, yet clear and lucid treatment of the rules and principles applicable to the law of international commercial transactions
Puan Shaizimah Badzri (Bacaan Asas FUU)/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 0389216390/ OC/ Bookline Services
Includes bibliographical references and index. (747-781 pages)
Keywords: Foreign trade regulation; Export sales contracts; Commercial law